2017
DOI: 10.1038/srep40947
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric footprint of the recent warming slowdown

Abstract: Growing body of literature has developed to detect the role of ocean heat uptake and transport in the recent warming slowdown between 1998–2013; however, the atmospheric footprint of the slowdown in dynamical and physical processes remains unclear. Here, we divided recent decades into the recent hiatus period and the preceding warming period (1983–1998) to investigate the atmospheric footprint. We use a process-resolving analysis method to quantify the contributions of different processes to the total temperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 37 publications
1
12
0
Order By: Relevance
“…Deep convective activity reaching the TTL in boreal summer is located primarily over the continents and their adjacent ocean north of 10 • N (see, e.g., Fig. 2 in Liu and Zipser, 2005). It should be noted that the climatological mean streamlines around 15 • N are connected to the stratosphere by crossing the tropopause (100 hPa) in boreal summer (see, e.g., Fig.…”
Section: Recent Decadal Changementioning
confidence: 96%
See 1 more Smart Citation
“…Deep convective activity reaching the TTL in boreal summer is located primarily over the continents and their adjacent ocean north of 10 • N (see, e.g., Fig. 2 in Liu and Zipser, 2005). It should be noted that the climatological mean streamlines around 15 • N are connected to the stratosphere by crossing the tropopause (100 hPa) in boreal summer (see, e.g., Fig.…”
Section: Recent Decadal Changementioning
confidence: 96%
“…The Hadley circulation is usually represented by a pair of thermally direct cells, symmetric about the Equator, with rising motion over the equatorial belt and sinking motion over the subtropics, with noticeable seasonal variability (e.g., Dima and Wallace, 2003). The mean meridional circulation driven by extreme deep convection further penetrates up to the tropical tropopause (Liu and Zipser, 2005). Here we first investigate the different modes of variability in mean meridional circulation and their relationship with Hadley cells during the boreal summer, focusing on the vertical structure including the lower stratosphere.…”
Section: Ascending Branch Of the Hadley Circulationmentioning
confidence: 99%
“…The carbon dioxide in the atmosphere has increased monotonically over the past century (Stocker et al ., ) and is considered to be responsible for global warming. However, global mean surface air temperature (SAT) did not rise significantly since the late 1990s, which contradicted the global warming theory based on greenhouse gas increase (Stocker et al ., ; Steinman et al ., ; Huang et al ., ; Guan et al ., ; Liu and Zhou, ). This decadal signal of cooling phenomenon drew the attention of the public (Easterling and Wehner, ; Kaufmann et al ., ; Li et al ., ), and was named global warming hiatus (Fyfe et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…So far, numerous studies have explored the mechanisms of the warming hiatus and revealed it is strongly correlated with the internal climate variability (ICV; Kosaka and Xie, ; Dai et al ., ; Guan et al ., ; Fyfe et al ., ; Huang et al ., ; Meehl et al ., ; Liu and Zhou, ), such as the Inter‐decadal Pacific Oscillation (L'Heureux et al ., ; Dai et al ., ; Meehl et al ., ), the cooling of the La Niña‐like event (Kosaka and Xie, ), the negative phase of the North Atlantic Oscillation (NAO; Higuchi et al ., ; Huang et al ., ; Luo et al ., ), and the neutral Atlantic Multi‐decadal Oscillation (AMO; Wyatt et al ., ; Tung and Zhou, ). On the other hand, from the view of energy balance, a few studies indicated that heat was stored in the deeper Atlantic Ocean and southern oceans during the warming hiatus (Chen and Tung, ; ; Xie et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…The most recent hiatus ended around 2013 followed by a large warming due to an El Niño event in 2015 (Hu and Fedorov, 2017;Liu and Zhou, 2017;Urabe et al, 2017;Xie and 10 Kosaka, 2017). However, the El Niño of 2015/16 was different from the previous large 1997/98 El Niño with less warming in the eastern Pacific (Paek et al, 2017), conforming to an increasing trend of the central Pacific-type El Niño (Kao and Yu, 2009;Johnson, 2013).…”
Section: Introductionmentioning
confidence: 99%